Figurative language in online video game reviews - Merkl, Petr (Univerzita Pardubice, 2019)
This bachelor thesis deals with figure of speech known as metaphor and its occurrence in the genre of online game reviews. The figure is defined according to the conceptual theory. Special importance is ascribed to the differences in the way these figures areused in reviews for different age groups.
Figurativní jazyk v recenzích online video her
Keywords: figurative language; metaphor; conceptual metaphor; online game review; children; adults; figurativní jazyk; metafora; konceptuální metafora; online recenze videoher; děti; dospělí